City making : building communities without building walls - Frug, Gerald E., 1939- (Princeton University Press, 2001)
American metropolitan areas today are divided into neighborhoods of privilege and poverty, often along lines of ethnicity and race. City residents traveling through these neighborhoods move from feeling at home to feeling like tourists to feeling so out of place they fear for their security. As Gerald Frug shows, this divided and inhospitable urban landscape is not simply the result of individual choices about where to live or start a business. It is the product of government policies--and, in particular, the policies embedded in legal rules. A Harvard law professor and leading expert on urban.